Effect of high intensity interval training on antioxidant status, inflammatory response and muscle damage indices in endurance team male players - Sarkar, S.; Debnath, M.; Das, M.; Bandyopadhyay, A.; Kr Dey, S.; Datta, G. (Apunts Medicina de l'Esport, 2021)
High-intensity interval training (HIIT) has previously been reported having the effect of training period on altering oxidant status, muscle damage and performance. The present study was aimed to understand and evaluate the adaptive response of 8 weeks HIIT on muscle damage indices, inflammatory markers, oxidative stress variables and physical fitness parameters. Methods: Forty young endurance male players [i.e., football (n=20) and field hockey (n=20)] were recruited under two groups i.e., control and HIIT. 8 weeks long 3h/day of sprint-HIIT was intervened for thrice/week. HIIT workouts includes total 4 sets/session (divided into 2 phase×2 sets×2min) of all-out sprint workout (at 90-95% of HRmax with work: rest=1:1). Muscle damage indices (CK and LDH), inflammatory markers (IL-6 and TNF-a), oxidative stress variables (MDA, SOD, GSH and GPx) and physical fitness variables (VO2max, Wpeak and VJ) were assessed via following standard protocols. Result: The HIIT resulted to significantly(p<0.001) increase BMI (1.1%), LDH (15.0%), CK (14.4%), cortisol (9.4%), IL-6 (15.7%), TNF-a (18.2%), MDA (29.5%), VO2max (13.6%), Wpeak (11.6%), VJ (11.2%) and GPx (0.4%) along with significant (p<0.001) reduction in BF% (7.6%), SOD (11.1%), GSH (10.8%) content of athletes. Conclusion: Antioxidant redox imbalance confers inflammatory oxidative stress condition which further leads to muscle damage and that may cause due to HIIT induced temporary hypoxic condition which contrarily induced overtraining effect but with improving performance variables.